Pengaruh Praktik Internet Financial Reporting (Ifr) Terhadap Nilai Pasar Perusahaan (Studi Empiris Pada Perusahaan Lq45 Yang Terdaftar Di Bursa Efek Indonesia) - Dian Annisa Putri; Khairunnisa Harahap; Akmal Huda Nasution (Universitas Negeri Medan (UNIMED), 2019)
Abstract : The problem in this research is the advancement of technology to make the company that makes official website in disclosing financial and nonfinancial information, Internet change the presentation of company information. This research aims to determine the influence of Internet Financial Reporting practices on the market value of LQ45 decisively company listed on the Indonesia Stock Exchange (IDX) period 2018. The population of this research is 50 LQ45 companies listed on the Indonesia Stock Exchange (IDX) period 2018. The sampling method used is purposive sampling, with a sample number of 32 companies. The data analysis technique in this study is a double linear regression analysis. An independent variable is internet financial reporting. The research uses control variables i.e. EPS, Bvps, company size, profitability, liquidity, and leverage. The dependent variables in this study are the company's market value. The results in this study of internet financial reporting practices influenced the company's market value. Two control variables i.e. company size and profitability are influential to the company's market value. While the variable control eps, bvps, liquidity and leverage have no significant effect on the company's market value. The conclusion in this study is that internet financial reporting practices have significant effect on the company's market value. Variable size control firms and profitability have significant effect on the company's market value. However for variable control EPS, Bvps, liquidity, and leverage have no significant effect on the company's market value.Keywords: Internet Financial Reporting, Company market value